Strategic political authenticity: How populists construct an authentic image. - Holtz-Bacha, Christina (Cultures of authenticity, 2022)
The author addresses the relationship between populism and authenticity in the contemporary era. The author argues that for populists, authenticity is more than an image-building strategy and instead is used strategically to maintain a powerful emotional connection with supporters that extends beyond election campaigns. The chapter also examines the rise of a distinct populist style (ordinariness, provocation, a certain kind of intimacy) that is used in opposition to an established political class. This style is often represented, and celebrated, through social media and increasingly defines what it means to be authentic in the political sphere.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Election campaigns; Emotions; Political communication; Populism; Populist parties; Social media